Drugs quality control (Theoretical foundation and practical application) The Coursebook - Pleteneva, T. V.; Morozova, M.A.; Uspenskaya, E.V; Khatchaturyan, M.A.; Open Textbook Library (Open Textbook Library, 2019)
The Course book presents the basics of drugs quality control in accordance with regulatory documents (pharmacopoeia of Europe, USA, Japan, Russia) and new data from current scientific periodicals, monographs The features of the physical, spectral and chemical quality control of medicines according to the indicators (S0(Bidentification(S1(B, (S0(Btests(S1 (Band (S0(Bassay(S1 (Bare described in detail. Part II presents a workbook, which includes questions for the self-control of the material studied and tasks for a laboratory workshop. The Course book contains reference material and samples of pharmacopoeial articles. The Course book is designed for students of the specialty (S0(BPharmacy(S1(B.s
Module 1: General Questions of Drug Analysis and Quality Control -- Module 2: Physical Analysis for Medicines Quality Control -- Module 3: Water Quality Control -- Module 4: Chemical Analysis for Medicines Quality Control -- Module 5: Spectral Analysis for Drug Quality Control
In English.
Description based on online resource
Keywords: Medicine -- Textbooks